Sosialisasi Tanggap Bencana Banjir Aceh Tamiang Tahun 2025 - Diana Lestari; Meylissa Meylissa; Dewi Sartika (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Aceh Tamiang Regency is one of the regions in Aceh Province that is highly vulnerable to annual flooding due to river overflow and high rainfall intensity. Flood disasters often cause significant material and non-material losses, which are exacerbated by the limited public understanding of flood mitigation, early warning signs, and appropriate self-rescue procedures. This community service activity aims to increase public awareness, knowledge, and preparedness in facing flood threats through disaster mitigation socialization programs. The method applied in this activity includes participatory socialization, interactive discussions, and simulations of emergency response actions involving local communities, village officials, and volunteers. The program emphasizes recognizing early signs of flooding, understanding emergency evacuation routes, and improving coordination during disaster response. The results indicate a significant improvement in community knowledge regarding flood risks, early warning indicators, and emergency measures that should be taken before and during flooding events. Furthermore, the activity successfully strengthened coordination between village authorities and local volunteers in managing emergency response posts and distributing aid effectively. Through this socialization program, the community of Aceh Tamiang is expected to develop greater disaster resilience and preparedness. Increased awareness and coordinated response mechanisms are anticipated to minimize the adverse impacts of future flooding events, thereby reducing potential losses and enhancing community safety.